Management of the Expected Difficult Airway with Planned One-Lung Ventilation: A Retrospective Analysis of 44 Cases - Irouschek, Andrea; Schmidt, Joachim; Ackermann, Andreas; Moritz, Andreas; Trufa, Denis; Sirbu, Horia; Golditz, Tobias (Thoracic and Cardiovascular Surgeon, 2024)
Background Difficult airway management is essential in anesthesia practice. Particular challenges are posed to patients who require intraoperative one-lung ventilation. Specific guidelines for these scenarios have been lacking. The recent update of German guidelines incorporates recommendations for securing the airway in anticipated difficult airway scenarios in patients requiring one-lung ventilation. However, scientific data on this specific topic is rare. Methods A retrospective analysis was conducted on adult patients undergoing thoracic surgery with one-lung ventilation from 2016 to 2021. During these years, the standard of practice has been in line with the now published guidelines. Patients with anticipated difficult airways were identified, and airway management strategies were analyzed. Results Among 3,197 anesthetic procedures, 44 cases involved anticipated difficult airways, primarily due to prior head and neck tumor treatment. Nasal bronchoscopic awake intubation followed by oral reintubation under videolaryngoscopic inspection and the use of bronchial blockers was the standard procedure. No severe complications were recorded, and one-lung ventilation was maintained successfully in all cases. Discussion The study highlights the challenges of managing difficult airways during thoracic surgery. Recommendations align with recent guidelines, emphasizing the importance of tailored approaches. The use of single-lumen tubes with bronchial blockers appears favorable over double-lumen tubes, offering comparable ventilation quality with reduced risks. Conclusion Despite limitations, the study underscores the safety and efficacy of tailored airway management strategies during one-lung ventilation in patients with anticipated difficult airways. The presented approach offers patient safety and practicability. Further multicenter studies are warranted to validate these findings and refine clinical approaches.
CRIS-Team Scopus Importer:2024-11-29
Keywords: airway (includes related subject matter); anesthesia (includes related subject matter); practice guidelines; thoracoscopy/VATS; ventilation